THE EXPECTED ROLE OF INTEGRATED REPORTS IN REDUCING THE ASYMMETRY OF ACCOUNTING INFORMATION IN IRAQ - Hussein Ali Hisab (Scholar Express Journals, 2024)
The main objective of the research study is to determine the extent to which the expected role of integrated reporting will reduce Iraq's level of accounting information asymmetry. To this end, the researcher relied on a distributed questionnaire (Report Users, Financial Analysts, Faculty) and research has found a moral impact between integrated reports and reducing the asymmetry of Iraq's accounting information, Integrated business reports help reduce problems of accounting asymmetry through improved transparency and accountability and provide a more comprehensive picture of the company's performance by linking financial performance to non-financial performance and thus communicating information to all parties; The research recommends that integrated business reports should be adopted across Iraq's various sectors to reduce the similarity of accounting information and improve investors' decisions
Keywords: Integrated report; Asymmetry of Accounting Information; Financial performance